A Case Study of Women’s Health in Malé, Republic of Maldives - Usman, Asrath (Curtin University, 2016)
This thesis investigates and documents women’s health needs and concerns in Malé city, Maldives. A sequential mixed method design with both qualitative and quantitative research method was employed. Women’s health remained fundamentally connected to critical social determinant factors including education, economics, living condition, gender relations and health and social systems. Health policy affecting women need to shift beyond a conventional biomedical approach to align and incorporate critical and inter-related social determinants of health.